2011
DOI: 10.1063/1.3552983
|View full text |Cite
|
Sign up to set email alerts
|

Electron density and temperature of gas-temperature-dependent cryoplasma jet

Abstract: A microsize cryoplasma jet was developed and analyzed at plasma gas temperatures ranging from room temperature down to 5 K. Experimental results obtained from optical emission spectroscopy and current–voltage measurements indicate that the average electron density and electron temperature of the cryoplasma jet depend on the gas temperature. In particular, the electron temperature in the cryoplasma starts to decrease rapidly near 60 K from about 13 eV at 60 K to 2 eV at 5 K, while the electron density increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Cryoplasma jet , was utilized for the reduction of the auric ions at the interface with the frozen solution. The photograph of the cryoplasma jet is illustrated in Figure b, and the detailed schematic of the experimental setup is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Cryoplasma jet , was utilized for the reduction of the auric ions at the interface with the frozen solution. The photograph of the cryoplasma jet is illustrated in Figure b, and the detailed schematic of the experimental setup is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding de Broglie wavelength λ dB = 1 nm and kinetic energy E k0 = 0.813 meV. The ion beams are extracted from a cryo-plasma [59,60], and then, the beams are collimated to the required energy, in an experiment that is currently under development in our laboratory. Usually, these experiments are performed in high vacuum (<10 −7 mbar) to minimize dissipation through ion-atom collisions.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the cryoplasma chamber system have been introduced elsewhere. 9,11,12,17,24) The DBD electrode was a parallel-plate configuration made of stainless steel electrodes with dimensions of 10 × 5 mm 2 and polyimide sheets with a thickness of ∼0.125 mm placed on the surfaces of both electrodes, thereby acting as dielectrics. The discharge gas gap between the polyimide sheets was 0.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…7) The gas temperature in plasmas has not been considered as a crucial parameter in the research field of low-temperature plasmas since it does not vary under conventional low-pressure conditions; however, studies using gas temperatures controlled under temperature conditions lower than RT, named "cryoplasmas", have pointed out that the gas temperature should be treated as an important parameter from experimental results showing dynamic variations in physical characteristics, for example, self-organized patterns. [8][9][10][11][12] In addition to the viewpoint of scientific interest, for industrial applications, cryoplasmas are highly expected to be one of the key plasma technologies in areas such as plasma biomedical applications, which treat highly heat-sensitive materials, 13,14) and next-generation semiconductor device fabrication since the reductions in plasma gas and substrate temperatures have already shown the feasibility of decreasing the low-k material damage in the ashing process 15) and improving the trench profile in high-aspect-ratio plasma etching. 16) Recently, we have found that the total chemical reaction system in cryoplasmas also varies dynamically following a change in gas temperature due to changes in reaction rate coefficients, transport parameters, and gas compositions.…”
Section: Introductionmentioning
confidence: 99%